Acupuncture performed around the time of embryo transfer: a systematic review and meta-analysis. Issue 3 (March 2019) - Smith, Caroline A.; Armour, Mike; Shewamene, Zewdneh; Tan, Hsiewe Ying; Norman, Robert J.; Johnson, Neil P.
Abstract: This was a systematic review and meta-analysis to examine the efficacy, effectiveness and safety of acupuncture as an adjunct to embryo transfer compared with controls to improve reproductive outcomes. The primary outcome was clinical pregnancy. Twenty trials and 5130 women were included in the review. The meta-analysis found increased pregnancies (risk ratio [RR] 1.32, 95% confidence interval [CI] 1.07–1.62, 12 trials, 2230 women), live births (RR 1.30, 95% CI 1.00–1.68, 9 trials, 1980 women) and reduced miscarriage (RR 1.43, 95% CI 1.03–1.98, 10 trials, 2042 women) when acupuncture was compared with no adjunctive control. There was significant heterogeneity, but no significant differences between acupuncture and sham controls. Acupuncture may have a significant effect on clinical pregnancy rates, independent of comparator group, when used in women who have had multiple previous IVF cycles, or where there was a low baseline pregnancy rate. The findings suggest acupuncture may be effective when compared with no adjunctive treatment with increased clinical pregnancies, but is not an efficacious treatment when compared with sham controls, although non-specific effects may be active in both acupuncture and sham controls. Future research examining the effects of acupuncture for women with poorer IVF outcomes is warranted.